VOCABULARY ACQUISITION FOR TODDLERS: IMPACTS OF INTERNAL AND EXTERNAL CIRCUMSTANCES - Qonita Naylilhusna (English Language Teaching Journal, 2023)
Children aged four and five served as the research subjects for the study "Vocabulary  Acquisition of Children in Roudlotut Taaibin (Non-Formal Education)". The goal of this study was to compare the amount of vocabulary learned by four- and five-year-old children who were categorized based on the terms they used. This research is descriptive qualitative since it looks at linguistic phenomena across a certain time period. According to the findings of this study, four-year-olds acquire more vocabulary than five-year-olds do. On average, four- and five-year-olds acquire 100 more words in just eight minutes. Furthermore, the nouns that they occupied in the first sequence were the most typical words that four- and five- year-old children learned. Verb, adjective, and other words were the last terms they were able to master. Keywords: Psycholinguistics, Vocabulary, Acquisition